BOOK REVIEW: The Origins and Dynamics of Inequality: Sex, Politics, and Ideology (By Jon D. Wisman, Department of Economics, The American University, Washington D.C.) - Choudhury, Masud (Journal of Critical Realism in Socio-Economics (JOCRISE), 2023)
This is an original contribution, explained in informative content, and written in lucid language that can be accessed by an informed reader. The author is Professor Jon D. Wisman of the Department of Economics, The American University, Washington D.C. U.S.A. a prominent academic in the field of economic philosophical methodology, history of economic thought, and economic history.